Antinociceptive and Anti-inflammatory effects of Hydroalcoholic extract of aerial parts of Thymus carmanicus in male mice - Nasri, Sima; Ahmadpour yazdi, Masoumah (Archives of Advances in Biosciences, 2018)
Differentspecies of Thymusare capable of producing various pharmacological effects. The present paper aimsto investigate the analgesic and anti-inflammatory effects of hydro-alcoholic extract of areal parts of Thymus Carmanicus Jalas.In this experimental research, using the formalin,writhing and tail immersion tests, anti-inflammatory effectswere studied in micebyxylene-induced ear edemaand mercury immersion methods. Male NMRI mice weighing 20-25g were dividedinto five groups: negative control, positive control and three experimental groups, being injectedintraperitoneally by 250, 500 and 1000 mg/kg of hydroalcoholic extracts of Thymus carmanicus. The most effective dose of the extract was selected for the possible involvement of opioidergic systems. Animalsubjects were studied by pretreatment of opioid antagonist, naloxone. The data were analyzed throughANOVA and Tukey's test.Results indicated that in the formalin test, thedoses of 500 and 1000 mg/kg of theextract significantly reduced the score of analgesic in experimental groups(P<0.001).Meanwhile, pretreatment with naloxone inhibited some of the extract induced antinociceptive effects in comparison to controlgroup.In writhing and hot tail immersion tests,all doses of theextract significantly alleviatedpain in experimental groups(P<0.01). Moreover, the xylene-induced ear edema (P<0.001)as well asfoot edema in mercury immersion method was considerably reduced(P<0. 05). This study not onlyshowedthathydroalcoholic extract of areal parts of Thymuscarmanicus hasanalgesic and anti-inflammatory effects but also indicated that some of the antinociceptive properties of Thymus carmanicus are mediated by opioidergic mechanism, which in turn validated the traditional uses of the plant in the treatment of pain.